Uji penggunaan pelepah pisang dan spon pada pengemasan bibit rumput laut Kappahycus alvarezii dalam mencegah ice-ice - Datangmanis, Adieng A. R.; Kreckhoff, Reni L.; Longdong, Sammy N. J. (e-Journal BUDIDAYA PERAIRAN, 2020)
This search aimed to determine the shelf life of seaweed seedlings that are packaged using banana and sponge fronds in Styrofoam, determine the best seaweed packaging media in preventing damage or disease when seedlings are planted. The study was conducted for 5 weeks, from January to February 2020. Observation of seaweed seedlings was conducted at the Laboratory of Fish Health, Environment and Toxicology, Faculty of Fisheries and Marine Sciences and planting tests were carried out in Arakan Village, Tatapaan District. South Minahasa Regency.The research method was carried out in the form of: packing Kappaphycus alvarezii seaweed, observing seaweed seeds and planting test. The experiment was designed according to a factorial completely randomized 3 x 3 design so that there were two factors tested in this experiment, namely the packaging medium factor and the shelf life. The packaging medium factor (A), consists of the level ie, (a1) control / without medium, (a2) banana fronds, (a3) sponge; while the shelf life factor (B), consists of three levels namely, (b1) 24 hours, (b2) 36 hours and (b3) 48 hours with three treatments and three replications so that the total number is 27 units of experiment with the number of seeds needed as much as 108 kg. The treatments taken are A: control, B: Packaging seaweed seeds with the addition of banana midrib, C: Packaging seaweed seeds with the addition of a sponge. The data obtained were analyzed ANOVA statistics for factorial RAL using the JMP (SAS-institute) statistical program. The results of the analysis of the variance showed that differences in treatment (the combination between the storage medium and the shelf life) had a very significant effect on differences in the texture and color of seaweed ("P" <0.0001). However, the effect of the storage medium factor on the texture of seaweed did not change significantly at the time of the change in the shelf life factor level ("P" = 0.1664).